Characterization, expression profiling, and functional analysis of a Populus trichocarpa defensin gene and its potential as an anti-Agrobacterium rooting medium additive - Wei, Hui (Sci Rep, 2019)
The diverse antimicrobial properties of defensins have attracted wide scientific interest in recent years. Also, antimicrobial peptides (AMPs), including cecropins, histatins, defensins, and cathelicidins, have recently become an antimicrobial research hotspot for their broad-spectrum antibacterial and antifungal activities. In addition, defensins play important roles in plant growth, development, and physiological metabolism, and demonstrate tissue specificity and regulation in response to pathogen attack or abiotic stress. In this study, we performed molecular cloning, characterization, expression profiling, and functional analysis of a defensin from Populus trichocarpa. The PtDef protein was highly expressed in the prokaryotic Escherichia coli system as a fusion protein (TrxA–PtDef). The purified protein exhibited strong antibacterial and antifungal functions. We then applied PtDef to rooting culture medium as an alternative exogenous additive to cefotaxime. PtDef expression levels increased significantly following both biotic and abiotic treatment. The degree of leaf damage observed in wild-type (WT) and transgenic poplars indicates that transgenic poplars that overexpress the PtDef gene gain enhanced disease resistance to Septotis populiperda. To further study the salicylic acid (SA) and jasmonic acid (JA) signal transduction pathways, SA- and JA-related and pathogenesis-related genes were analyzed using quantitative reverse-transcription polymerase chain reaction; there were significant differences in these pathways between transgenic and WT poplars. The defensin from Populus trichocarpa showed significant activity of anti-bacteria and anti-fungi. According to the results of qRT-PCR and physiological relevant indicators, the applied PtDef to rooting culture medium was chosen as an alternative exogenous additive to cefotaxime. Overexpressing the PtDef gene in poplar improve the disease resistance to Septotis populiperda.